In praise of suffering: the role of holistic thinking in meaning making and gratitude - Gan, Eunice Ghee Wu (Nanyang Technological University, 2023)
Through an experimental-causal-chain design, the present research sought to investigate how holistic thinking might influence gratitude through meaning-making. From past research, we know that holistic thinking and meaning-making are central to coping during times of suffering. However, causal links between holistic thinking, meaning-making, and gratitude in the context of suffering are understudied. Three studies were conducted with Singaporean samples to examine these links. In Study 1, we replicated a validated manipulation task to elicit holistic thinking, and meaning-making was measured. Statistical analyses revealed that the causal link between holistic thinking and meaning-making was inconclusive. In the pilot study for Study 2, we successfully developed a novel manipulation of meaning-making by manipulating the attention paid to meaning-making phrasings in a book association task. In Study 2, we manipulated meaning-making through the novel task developed and measured gratitude, but a causal link between meaning-making and gratitude was not sufficiently established. Null findings suggest that in the context of suffering, meaning-making could not sufficiently address the possible links between holistic thinking and gratitude. To explore reasons the present research was insufficient in establishing causal links between holistic thinking, meaning-making, and gratitude, implications of the null findings were discussed.